ChemInform Abstract: Cobalt‐Catalyzed Alkyne—Dihalomethane—Amine Coupling: An Efficient Route for Propargylamines. Issue 8 (1st March 2013) - Tang, Yanchi; Xiao, Tiebo; Zhou, Lei
Abstract The transformation can be made with the cheap CoBr2 in the absence of phosphine ligands and various functionalities are tolerated.